Narrations of Imam Al-Tirmidhi, May Allah Have Mercy on him, on the Time When Fighting is Recommended and what was Said about Superstition - An Analytical Study - Abu Bakr A. Hassan Jassim; Anwar Faris Abd (Islamic Sciences Journal, 2025)
ABSTRACT The research deals with the life of Imam al-Tirmidhi (may Allah have mercy on him), narrating the time when fighting is recommended and what was stated regarding superstition . I adopted the analytical inductive method in studying the life of Imam al-Tirmidhi (may Allah have mercy on him) and his narrations. The number of hadiths was (5) with duplicates. After deleting the duplicates, I found (2). I studied them analytically, according to the steps and rules of scholarly hadiths. From the study, it became clear to me that Imam al-Tirmidhi (may Allah have mercy on him) was one of the most skilled compilers of Sunan, and his fame lay in his judgment of most of the hadiths he included, which distinguished him from other compilers. Many of the Tabi'un narrated from him, and he received praise from leading scholars in the field of hadith criticism and authentication. The research plan consisted of an introduction that addressed the importance of the topic, the reasons for choosing it, and previous studies on the subject , the difficulties he faced, the research methodology and structure, and its organization came as follows: The first section dealt with his personal and academic life, and in the second section his narrations on the time in which fighting is recommended and what was said about superstition.